CONTRIBUTION OF PALM SUGAR BUSINESS TO FARMERS INCOME IN SOUTH OKU REGENCY - Indriyani, Indriyani; Munajat, Munajat; Fifian Permata Sari (International Journal of Social Science, 2024)
The sub-districts of Mekakau Ilir, Banding Agung and Warkuk Ranau Selatan are several agricultural areas because approximately 70% of the population makes their living as coffee farmers, and within them there are sugar palm farmers in South OKU Regency. The majority of farmers choose to develop palm sap processing businesses compared to other businesses. Processing palm sap really helps the community in the community economy of South OKU Regency.  This research is aimed at analyzing the contribution of palm sugar business income to farmers' income in South Oku Regency. The research was carried out in March 2024 using survey research methods. The sampling method used was a simple random method with 52 palm sugar entrepreneurs taken as samples. The research result shows that the contribution of income from the palm sugar business to the total income of craftsmen's families is 24.00%. The contribution of income from palm sugar to the total income of craftsmen's families is in the low category because the contribution of palm sugar farming to total income is <33.3%.